Electrocoagulation and recovery of tannins from tree barks - Chowwanapoonpohn S. (2014)
The potential of electrocoagulation technique was investigated as a method of recovering or enriching phenolic compounds from the crude aqueous solution of tree bark extractive. The recovery method involved dissolving the coagulum in a dilute acid solution and extracting with an alcohol. Phenolic substances from selected tree barks were coagulated electrolytically and subsequently recovered as concentrated phenolic extracts with overall increase in antioxidant activity.